Aplikasi Penerimaan Mahasiswa Baru Online Dengan Sms Gateway di STMIK Indonesia Padang - Monanda Rio Meta; Ilham Eka Putra; Annisa Urfa (Ikatan Ahli Informatika Indonesia (IAII), 2018)
STMIK Indonesia Padang is one of the high school level education isntitutions in Padang. In Students admission activities, STMIK Indonesia is still announce the result conventionally, its affect the comfort of prospective students. Examinees have to wait until the reslut announced to know if they could register or not. There for, SMS Gateway system is neededto improve service to prospective students and improve the image of STMIK Indonesia Padang it self in society. This research intented to build a SMS Gateway aplication to help students admission activities at STMIK Indoenesia Padang. This SMS Gateway developed by waterfall method, with PHP programming language and Gamu aplication to integrate the System to SMS Gateway and tested with black box method. The result is a SMS Gateway Information System to inform students passing grade.